PROGRAMME NATIONAL DE GESTION DE L’ENVIRONMENT URBAIN POUR LA PERIODE 1996-2010 EN COTE D’IVOIRE: REGARD DES POPULATIONS DES QUARTIERS PRÉCAIRES DE LA VILLE D’ABIDJAN - Kassoum, Traore (European Scientific Journal, ESJ, 2012)
The environmental situation in the cities of Côte d’Ivoire and particularly in Abidjan is a concern for the general population because of the problems that threat. These problems include waste management, street sweeping, cleaning of drains, maintenance of public gardens and lagoon banks. In addition to these problems, there is also the occupation of sidewalks and public domain, congestion of roads and stray animals in some neighborhoods. Similarly, population growth and the urban fabric have a great importance in the choice of environmental management in general and waste in particular. Furthermore, the non delineation of habitat types, classes of population, commercial and industrial areas often does not favor good control of sanitation and management system. Some isolated neighborhoods and not walkable in all seasons do not receive waste collection services. The amount of waste produced is strongly related to life which leads inevitably to pollution in the city of Abidjan. In fact, the city of Abidjan as it is the case elsewhere in Africa has the same characteristics. Despite efforts by the authorities to provide a better living environment for people, there is still environment management crisis that reflects the health of the population and invalidates much of initiatives (programs and projects) for development. This situation of crisis justifies the interest of our reflexion about the national program for management of the urban environment defined for the period 1996-2010 and the appreciation made by population especially those living in precarious neighborhoods in precarity.